ANALISIS DAYA SAING BIJI KAKAO DI KABUPATEN BIREUEN - Yusdiana Yusdiana (Universitas Teuku Umar, 2017)
This study aims to analyze the competitiveness of cocoa commodities in Bireuen Regency. Primary data and secondary data relating to competitiveness in Bireuen District. PAM analysis is used in this research to analyze the level of competitiveness. The number of farmer sample taken in this research is 19 people determined by simple random sampling and merchant sample determined by simple random sampling method. The results show that cocoa commodity in Bireuen Regency has competitiveness seen from competitive advantage and comparative advantage. The analysis of competitive advantage consists of positive private gain (PP) and Privat Cost Ratio (PCR) of less than 1 that is 0.45 indicates that cocoa commodity in Bireuen Regency has competitive advantage. Comperative advantage analysis consisted of positive social benefit (SP) and Domestic Resource Cost (DRC) of less than 1 that is 0.28 indicates that cocoa commodity in Bireuen Regency has a competitive advantage.